Influence of Weight Loss on Skeletal Muscle Mitochondrial Function in the Mature Horse. (June 2014) - Zambito, J; Nichols, C; Barnes, K; Spooner, H; Hollander, J
Abstract : Introduction: Obesity creates many metabolic issues in horses, yet stepwise alterations in mitochondrial capacity and oxidant status during weight loss have not been assessed. Skeletal muscle contains subsarcolemmal (SSM) and interfibrillar (IFM) mitochondria, which respond differently to physiological stimuli, impacting tissue and systemic oxidant status. It was hypothesised that horses would display improved muscle mitochondrial subpopulation function in middle gluteal muscle, and decreases in circulating oxidant status markers during weight loss from an obese (7 to 8) to moderate (5) body condition score (BCS). Methods: 8 light‐type horses were studied. Mitochondrial subpopulations were isolated through differential centrifugation and all enzymatic activity through colorimetric kinematic assays. Effects of BCS reduction or percent weight loss were evaluated using SAS (mixed procedure with repeated measures). Results: Plasma nitrate decreased in response to BCS reduction (P = 0.06) and percent weight loss (P = 0.06), whereas erythrocyte total glutathione (P = 0.06) concentration increased with decreasing BCS. Mitochondrial electron transport chain complexes I and IV displayed greater activity in SSM than IFM (P≤0.03), while all complexes in IFM had decreased activity due to both weight parameters (P≤0.01). Interactions between subpopulation complex IV activity and weight loss markers (P<0.05) were displayed. Citrate synthase activity, indicating mitochondrial number, was greater in SSM than IFM (P<0.0001) but was unaffected with weight loss. Lipid peroxidation was decreased with BCS change (P = 0.01) and weight loss (P = 0.02), displaying greater amounts in SSM than IFM (P≤0.02). Conclusions: Alterations in complex activities and lipid peroxidation suggest IFM are more affected by weight loss, with large contributions from complex IV by‐products. Mitochondrial component flexibility may contribute individually to disease development and performance of equine athletes. Ethical Animal Research: The study was approved by the Middle Tennessee State University Institutional Animal Care and Use Committee.Sources of funding:  West Virginia University Summer Undergraduate Research Experience Program and Middle Tennessee State University.Competing interests:  none.